The LysR-type transcriptional regulator STY2660 is involved in outer membrane protein synthesis, bile resistance and motility in Salmonella enterica serovar Typhi - Gama-Martínez, Yitzel; Hernández, Victor M.; Encarnación-Guevara, Sergio; Martínez-Batallar, Ángel; Hernández-Lucas, Ismael (Frontiers in Microbiology, 2025)
Salmonella enterica serovar Typhi, the etiological agent of Typhoid fever in humans, contains 44 LysR-type transcriptional regulators (LTTRs), most of which are annotated as hypothetical proteins whose roles are not yet described. In this work we demonstrated by mutants, growth evaluation in bile salts, transcriptional fusions, EMSAs, outer membrane protein profiles and motility assays, that the S. Typhi LTTR STY2660 is involved in two regulatory networks: FNR-STY2660-OmpR-OmpC for porin synthesis and bile resistance and FNR-STY2660-OmpR-FliD for motility. Thus, the LTTR STY2660 is able to establish genetic communication with master regulatory proteins to promote and efficiently respond to adverse conditions present in the host.